Analysis of Sitting Pressure Distribution on Office Chair for Occupants with Different Body Mass Index - Li, Xiao; Zhang, Ting; Shen, Liming; Tor, Onder; Zhu, Yunlong; Zhang, Jilei; Chilufya, Chilufya; Yan, Bo; Hu, Lingling (Springer International Publishing, 2021)
The pressure distribution is one of popular objective measurements for sitting comfort, but a few studies were found for the pressure distribution between subjects with different body mass index and office chair . The effects of sitting posture, body mass index, gender, and the types of office chair (adjustable and non-adjustable) on sitting pressure distribution were investigated in this study. 18 subjects with different body mass indexes (overweight, normal weight and under weight) completed five different sitting postures in the order of forward-watching screen, forward-writing, backward-typing, backward-bow one’s head, and backward-cross legged. The outcome demonstrated that the seat adjustable or not, the type of sitting posture has significant influence on the average pressure, maximum pressure gradient and pressure distribution uniformity. Gender and body mass index have significant effects on the circular pressure gradient. Results of sitting pressure distribution obtained in this research, could strengthen the particularity of the body shape consideration in the design of office chairs.
Keywords: 2. Zero hunger